Antimicrobial Susceptibility Pattern of Gram-Negative Bacterial Isolates from Raw Chicken Meat Samples - Gautam, Neha; Poudel, Rojan; Lekhak, Binod; Upreti, Milan Kumar (Tribhuvan University Journal of Microbiology, 2019)
Objectives: This research aims to study the microbial quality of chicken meat available in retail shop of Kathmandu Valley. Methods: This Study was conducted from June to December 2018 in three different districts of Kathmandu Valley. Samples were collected in sterile plastic bags, labeled properly and stored in an icebox and transported to the Food Microbiology laboratory of Golden Gate International College. During sample preparation, 25 grams of each sample was taken and transferred to sterile flasks containing 225 ml of buffered peptone water. Potential pathogenic Gram-negative bacteria were isolated by using respective selective media and identified by biochemical test. Antibiotic susceptibility profile of isolates was carried out by Kirby-Bauer disc diffusion method according to CLSI 2017 guideline. Results: Of total 81 chicken meat samples processed; 201 Gram negative bacteria were isolated. E. coli (100%) was the dominant Gram-negative isolates, followed by Citrobacter spp (62.96%), Pseudomonas spp (40.74%), Proteus spp (19.75%), Salmonella spp (16.04%) and Klebsiella spp (8.64%) respectively. No any multidrug isolates were detected. Conclusion: The study showed that the raw chicken meat samples of Kathmandu valley was highly contaminated with Gram negative potential pathogenic bacteria. Antimicrobial resistance pattern shown by the isolates may indicates that there is not overuse of drug in animals and the less chance of risk of increasing antimicrobial resistance.